TARGET NEED INTERVIEW IN DEVELOPING TEACHING ENGLISH ESSAY MATERIAL BASED ON BRAINWRITING STRATEGY - Dini Fitriani; Yumna Rasyid; Ratna Dewanti (English Education Department, 2019)
The study in this research is an interview in needs analysis of students and lecturers or target needs to determine the basis to be used in developing a product in the form of teaching essays in English. Analysis of this need is a step or procedure that must be done in research and development. The procedure in this research is interview. This research was conducted at an English Education Program at STKIP Kusuma Negara Jakarta. One of the motivation of researcher to conduct this research is the existence of information on the ability of most students in writing English essays that are still below the average and one reason is because the English essay writing material used is less interesting and difficult to understand, so students not interested in studying thoroughly. With this, researcher was inspired to develop teaching material models for writing essays in English. One of the procedures carried out in developing the teaching material is needs analysis. Based on the target needs interview , the researcher found the characteristics of teaching materials in writing English essays needed by students and lecturers, these characteristics are almost similar to the characteristics of brainwriting learning strategies. Thus a brainwriting strategy will be integrated into the preparation of English essay writing teaching material.